The Analysis of Lean Manufacturing in Waste Reduction During Rosin Ester Production at PT XYZ - Naufal Dhiya Hibatullah; Adi Djoko Guritno; Arita Dewi Nugrahini (Agroindustrial Journal, 2022)
Waste are commonly generated during the utilization of raw materials. Therefore, they are become important to consider lean manufacturing to achieve the overall business objectives. PT XYZ is a major company in processing pine resin and its derivatives, including gum rosin, turpentine and rosin ester, mainly used as featured commodities. During production, a certain amount of unwanted materials in the form of defect and in the form of work-in-process (WIP) that caused waiting wastes are obtained, particularly at the rosin ester floor. This study aims to identify the waste types and their dominant factors that caused waste occurred in PT XYZ, as well as recommend improvement strategies in boosting production efficiency. Based on the identification results, two dominant wastes occurred in the form of defects and waiting. The defect and scrap portions were prevalent in gum rosin drops, flakes, brushed dust and products that did not fulfill color and size specifications at 63.72 kg/shift that equal to 2,08% scrap rate per shift. Meanwhile, waiting waste refers to work-in-process (WIP) on Oleo Pine Resin (OPR) storage and delay interval for a complete sampling process. The WIP circumstance was also observed at the packaging workstation. Furthermore, repairing tank leaks, allocating special workers to flaking workstations, extending workers’ supervision, combining flake cooling and transportation processes, procuring cooling conveyors and increasing the quantity of esterification reactors were recommendations for optimum production. These proposed activities have the capacity to enhance the process cycle efficiency (PCE) value from 4.65 to 6.34%.